Study on Installation of Neutral Ground Resistance in Very Small Power Plant Transformer - Pathomthat Chiradeja; Chaichan Pothisarn; Panu Srisuksai; Suntiti Yoomak; Atthapol Ngaopitakkul; Natthanon Phannil (2022 IEEE Industry Applications Society Annual Meeting (IAS), 2022)
Faults in the distribution system of the Thai electrical system occur frequently. Such faults directly affect the protective equipment of the distribution system. The protective device disconnects the circuit unnecessarily on many occasions because it detects a higher current than expected. In this study, a 22-kV distribution system and a very small power plant (VSPP) were connected. The system consists of two feeders. Feeder 1 supplies electricity directly to the load; a fault was enforced in this feeder. Feeder 2 supplies electricity directly to the load; the VSPP was connected to this feeder. The fault in Feeder 1 was simulated, and the behavior of the defense system was studied. Unnecessary disconnection of the VSPP circuit took place because the high fault current caused the overcurrent protection relay to operate instantaneously. Therefore, a neutral ground resistance was installed at the VSPP transformer to reduce the fault current, extend the relay operating time to the delay range, and reduce unnecessary disconnections of the overcurrent protection relay of the VSPP. In addition, when a fault occurs in the distribution system, the faulted phase voltage decreases, whereas the non-faulted phase voltage increases. Surge arresters and voltage transformers must be able to withstand an increase in voltage. This is also explained and discussed in this paper.
Keywords: Power Systems Fault Detection; Islanding Detection in Power Systems; Electrical Fault Detection and Protection